2011
DOI: 10.2106/jbjs.j.00416
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization in External Rotation After Primary Shoulder Dislocation Did Not Reduce the Risk of Recurrence

Abstract: Immobilization in external rotation does not reduce the rate of recurrence for patients with first-time traumatic anterior shoulder dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 20 publications
3
125
2
2
Order By: Relevance
“…Rhon and Hando for their interest and insightful comments regarding our recently published study. While we would wholeheartedly agree that a period of immobilization longer than the 3 or 4 weeks employed in our study and others [1][2][3] would be beneficial to soft tissue healing, the practicalities of doing so may limit its utility. According to our (as well as Professor Itoi's) observations, compliance with brace wear was a time-limited phenomenon.…”
Section: To the Editormentioning
confidence: 49%
“…Rhon and Hando for their interest and insightful comments regarding our recently published study. While we would wholeheartedly agree that a period of immobilization longer than the 3 or 4 weeks employed in our study and others [1][2][3] would be beneficial to soft tissue healing, the practicalities of doing so may limit its utility. According to our (as well as Professor Itoi's) observations, compliance with brace wear was a time-limited phenomenon.…”
Section: To the Editormentioning
confidence: 49%
“…One randomized controlled trial has supported the use of external rotation braces applied on the day of dislocation at reducing the risk of recurrence from 42% to 26% (p ¼ 0.033) over 2 years 23 Two further randomized controlled trials, however, have failed to show a benefit of external rotation bracing 24,25 Summary: The evidence for external rotation splintage is equivocal. In the cohort of patients in whom recurrent instability is most likely, external rotation gave no additional benefit over simple immobilization in a sling.…”
Section: Further Investigationsmentioning
confidence: 99%
“…We applaud the efforts of this research team, as well as others [3,9] who have attempted to reproduce the results found by Itoi et al [8,10] with randomized clinical trials. However, the results of these three studies still leave questions regarding the ideal method for shoulder immobilization in this population.…”
Section: To the Editormentioning
confidence: 73%